The Bounty from the Beach Cross-Cultural and Cross-Disciplinary Essays - Largeaud-Ortega, Sylvie (ANU Press, 2018)
"The Bounty from the Beach is a collection of cross-disciplinary essays, capitalising on a widely shared fascination for the Bounty story in order to draw scholarly attention to Oceania. It aims to reorient the Bounty focus away from the West, where most Bountynarratives and studies have emerged, to the Pacific, where most of the original events unfolded. It investigates the Bounty heritage from the standpoint of the beach, Greg Dening's metaphor for culture contact and conflict in the Pacific Islands: this liminal place that transforms Islanders and voyagers, islands and ships, each time it is crossed. It analyses the way newcomers create new islands, and how these changes may occasionally impact the world. This volume examines the 'little people', to use another of Dening's expressions, who stand 'on both sides of the beach': they are Polynesian or European or, as beaches are crossed and remade, no longer one without the other, but bound together in processes of change. Among these people are Bounty sailors, beachcombers, Pitcairners and indigenous Pacific Islanders of the past and the present. This collection also explores the works of some renowned Western writers and actors who, turning mutineers after their own fashion and in their own times, themselves crossed the beach and attempted to illuminate the 'little people' involved in the Bounty narratives. These prominent writers and actors put the spotlight on characters who were silenced on account of race, class or geographical distance from the dominant centres of power. Inspired by Dening's empowering voice, our purpose is to fill that silence. Just as it criss-crosses the ocean, progressing with the ship through time and space, The Bounty from the Beach ranges far and wide across disciplines, methodologies and scholarly styles. Its multidisciplinary course contributes to illuminate the multiple ways in which the Bounty heritage embraces diverse horizons. It throws light on the colonial discourse that undertook to stifle Pacific Islander agency, and the neocolonial policies that have been applied to Oceania, and still are: hegemonic moves that have led to global environmental, nuclear and ecological hazards. As a whole, the collection contends that what unfolds in this vast ocean matters: the stakes are high for the whole human community."